2022
DOI: 10.3389/fvets.2022.878240
|View full text |Cite
|
Sign up to set email alerts
|

Bovine Coronavirus Infects the Respiratory Tract of Cattle Challenged Intranasally

Abstract: Bovine Coronavirus (BCoV) is a member of a family of viruses associated with both enteric and respiratory diseases in a wide range of hosts. BCoV has been well-established as a causative agent of diarrhea in cattle, however, its role as a respiratory pathogen is controversial. In this study, fifteen calves were challenged intranasally with virulent BCoV in order to observe the clinical manifestation of the BCoV infection for up to 8 days after initial challenge, looking specifically for indication of symptoms,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 50 publications
1
3
0
Order By: Relevance
“…Although BCoV is associated with enteric disease due to its dual tropism for the respiratory and digestive systems 61 , this virus was only amplified from the DNS of one calf that was simultaneously infected with OvGHV2 without being detected from the intestinal and fecal samples evaluated. Accordingly, these findings confirmed that BCoV was associated only with the development of the pulmonary distress syndrome herein described; similar results were previously described 31,58,60,62,63 .…”
Section: Discussionsupporting
confidence: 92%
“…Although BCoV is associated with enteric disease due to its dual tropism for the respiratory and digestive systems 61 , this virus was only amplified from the DNS of one calf that was simultaneously infected with OvGHV2 without being detected from the intestinal and fecal samples evaluated. Accordingly, these findings confirmed that BCoV was associated only with the development of the pulmonary distress syndrome herein described; similar results were previously described 31,58,60,62,63 .…”
Section: Discussionsupporting
confidence: 92%
“…The BCoV can trigger simultaneous infections with secondary pathogens, such as Pasteurella multocida and other respiratory pathogens, which may cause respiratory disease complex and severe pneumonia [ 32 33 ]. Soules et al [ 38 ] challenged calves intranasally with virulent BCoV to investigate the clinical signs and tissues harboring BCoV. The results indicated that respiratory signs developed, such as nasal discharge and coughing, and the upper respiratory tissue was infected with BCoV because viral shedding was detected in the nasal and bronchoalveolar lavage for at least seven days after the initial challenge.…”
Section: Discussionmentioning
confidence: 99%
“…GI (GIa-Classical strains, GIb-European strains) and GII (GIIa -Korean strains, GIIb-America/Asia strains [ 21 27 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…These losses result from the generalized state of immunosuppression of the animal, favoured by the stress during handling together with environmental factors that contribute to the establishment of its multifactorial aetiology (Fulton et al 2022 ; Gaudino et al 2022 ). The viruses mainly associated with the BRD are bovine herpesvirus-1, the cause of the infectious bovine rhinotracheitis (IBR) (Jones and Chowdhury, 2007 , 2010 ); bovine parainfluenza virus-3 (BPIV-3) (Bryson et al, 1979 ; Mehinagic et al 2019 ); bovine viral diarrhoea virus 1 and 2 (BVDV-1–2) (Burciaga-Robles et al 2010 ; Goto et al 2021 ); bovine respiratory syncytial virus (BRSV) (Fulton et al 2000 ; Sorden et al 2000 ; Makoschey and Berge 2021 ); bovine adenovirus A–D (BAdV-A–D) (Fent et al 2002 ; Fulton, 2009 ) and bovine coronavirus (BCoV) (Storz et al 1996 ; Frucchi et al 2022 ; Soules et al, 2022 ). The associated bacteria belong to the Pasteurellaceae Family Mannheimia haemolytica (Rice et al 2007 ; Confer and Ayalew.…”
Section: Introductionmentioning
confidence: 99%